Substrate Complexity Drives Hermit Crab (Diogenidae) Diversity and Ecological Flexibility Across Sand, Rubble, and Coral Habitats in Tarahan Island, Indonesia - Prakas Santoso; Melly Nurseha; Chentia A. Rini; Arief Budi; Hanisya Aurora; Muhammad A. Zaidaniansyah; Afifah N. Hasanah; Nurlita P. Anggraini; Aziz Budiman; Agitha S. Jasmine; Raissha A. Siregar; Ulil Amri (Aceh Journal of Animal Science)
Research on the role of benthic substrates in shaping hermit crab communities along coastlines remains relatively limited, despite the important role this group plays in coastal benthic ecosystems. This study counducted in April 2025, aimed to examined the relationship between substrate characteristics sand, coral rubble, and coral reefs and the distribution and community structure of hermit crabs of the family Diogenidae along the northwestern coast of Tarahan Island, Indonesia. A total of 58 individuals consisting of 9 hermit crab species were identified across the three habitat types, with the highest species richness and abundance found in the rubble habitat, which exhibited high porosity and microhabitat heterogeneity. Community analysis using ANOSIMS  showed R value of -0.002 and a p-value of 0.48 revealed an overlap in species composition among habitat types however, SIMPER analysis certain species such as Clibanarius striolatus consistently dominated habitats with high structural complexity, while others like Clibanarius signatus showed a specific preference for coral-sand habitats. This variation in habitat preference reflects a spectrum of ecological strategies, ranging from specialists to generalists, within the hermit crab community studied. The findings highlight the importance of substrate diversity and integrity in supporting the ecological flexibility, stability, and sustainability of hermit crab communities in dynamic coastal ecosystems